1993
DOI: 10.1182/blood.v81.1.15.bloodjournal81115
|View full text |Cite
|
Sign up to set email alerts
|

Biologic response to anti-CD16 monoclonal antibody therapy in a human immunodeficiency virus-related immune thrombocytopenic purpura patient

Abstract: A patient with refractory human immunodeficiency virus (HIV)-related immune thrombocytopenic purpura (ITP) was treated with 3G8 (anti-CD16) monoclonal antibody on days 1, 3, and 8 (25, 25, and 50 mg were administered intravenously, respectively). Side effects were those expected after the administration of a xenogenic protein, but a severe bone pain occurred from the second injection. At the time of the initiation of the treatment the platelet count was 20,000/mm3 and the absolute CD4 number was 100/mm3. We ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Previous work from our laboratory has demonstrated that neonatal Mo express adult levels of FccRI and FccRII (10) and show normal attachment and ingestion of IgG anti-Rh(D)-coated red cells (35). Earlier studies have suggested the involvement of FccRIIIa in immune platelet clearance in vivo (15,16). Hence, anti-HPA-1a-sensitised platelets might preferentially interact with the circulating FccRIII-positive Mo subpopulation (36,37) which is reduced in cord blood (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work from our laboratory has demonstrated that neonatal Mo express adult levels of FccRI and FccRII (10) and show normal attachment and ingestion of IgG anti-Rh(D)-coated red cells (35). Earlier studies have suggested the involvement of FccRIIIa in immune platelet clearance in vivo (15,16). Hence, anti-HPA-1a-sensitised platelets might preferentially interact with the circulating FccRIII-positive Mo subpopulation (36,37) which is reduced in cord blood (38).…”
Section: Discussionmentioning
confidence: 99%
“…(14). Moreover, anti-FccRIII mAb 3G8 decreased the elimination of immune complexes on administration to chimpanzees (14) and was moderately bene®cial in the treatment of patients with chronic ITP (15,16). More recently the role of the human FccRIIa in the immune clearance of platelets was demonstrated in a transgenic mouse model (17).…”
mentioning
confidence: 99%
“…Clarkson et al (1986) also demonstrated that RBCs opsonized with IgG had an increased clearance time after treatment of the patient with anti-FcRIII mAb, suggesting that platelet destruction may be due, at least in part, to low affinity Fc receptors. Soubrane et al (1993) used the same anti-FcRIII mAb 3G8 to treat a patient with refractory human immunodeficiency (HIV)-related ITP, and the patient subsequently had long-term correction of the thrombocytopenia. Some of the toxicity described with the use of the mAb 3G8 (Clarkson et al, 1986;Soubrane et al, 1993) may have been due to the fact that 3G8 could have bound to the soluble form of FcRIII, resulting in immune complex formation.…”
Section: Discussionmentioning
confidence: 99%
“…Soubrane et al (1993) used the same anti-FcRIII mAb 3G8 to treat a patient with refractory human immunodeficiency (HIV)-related ITP, and the patient subsequently had long-term correction of the thrombocytopenia. Some of the toxicity described with the use of the mAb 3G8 (Clarkson et al, 1986;Soubrane et al, 1993) may have been due to the fact that 3G8 could have bound to the soluble form of FcRIII, resulting in immune complex formation. A soluble form of FcRI (CD64) has not been described, and immune complex formation should therefore not be a complication with the use of anti-FcRI antibody.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation